Zur Identität der aus Madagaskar beschriebenen Autoserica stupida Brenske, 1900 (Coleoptera: Scarabaeidae: Sericini). - Ahrens, Dirk (Contributions to Entomology = Beiträge zur Entomologie, 2003)
A revision of the type material of species described as Autoserica Brenske, 1897 from the Malagasy region confirmed the conspecificity of Autoserica stupida Brenske, 1900 with the Oriental species Maladera straba (Brenske, 1898) comb. n. The following four new synonyms and two new combinations are established: Maladera straba (Brenske, 1898) comb. n. (= Neoserica apogonoides Brenske, 1898, syn. n., = Autoserica stupida Brenske, 1900, syn. n., = Neoserica sumatrensis Brenske, 1898, syn. n., = Neoserica pavieana Brenske, 1899, syn. n.), Maladera detersa (Erichson, 1834) comb. n. The systematic position and distribution of the species are discussed. A lectotype is designated for M. detersa (Erichson). Keywords Coleoptera, Scarabaeidae, Sericini, Madagaskar, Oriental region, new synonymy, new combinations, distribution. Nomenclatural Acts stupida Brenske, 1900 (Autoserica), syn. n. of Maladera straba (Brenske, 1898) detersa (Erichson, 1834) (Maladera), Lectotype; comb. n. hitherto Serica detersa straba (Brenske, 1898) (Maladera), comb. n. hitherto Autoserica straba apogonoides Brenske, 1898 (Neoserica), syn. n. of Maladera straba (Brenske, 1898) pavieana Brenske, 1899 (Neoserica), syn. n. of Maladera straba (Brenske, 1898) sumatrensis Brenske, 1898 (Neoserica), sysn. n. of Maladera straba (Brenske, 1898)